Boron Difluoride Curcuminoid Fluorophores with Enhanced Two‐Photon Excited Fluorescence Emission and Versatile Living‐Cell Imaging Properties. Issue 15 (25th February 2016) - Kamada, Kenji; Namikawa, Tomotaka; Senatore, Sébastien; Matthews, Cédric; Lenne, Pierre‐François; Maury, Olivier; Andraud, Chantal; Ponce‐Vargas, Miguel; Le Guennic, Boris; Jacquemin, Denis; Agbo, Peter; An, Dahlia D.; et al.
Abstract: The synthesis of boron difluoride complexes of a series of curcuminoid derivatives containing various donor end groups is described. Time‐dependent (TD)‐DFT calculations confirm the charge‐transfer character of the second lowest‐energy transition band and ascribe the lowest energy band to a "cyanine‐like" transition. Photophysical studies reveal that tuning the donor strength of the end groups allows covering a broad spectral range, from the visible to the NIR region, of the UV–visible absorption and fluorescence spectra. Two‐photon‐excited fluorescence and Z‐scan techniques prove that an increase in the donor strength or in the rigidity of the backbone results in a considerable increase in the two‐photon cross section, reaching 5000 GM, with predominant two‐photon absorption from the S0 –S2 charge‐transfer transition. Direct comparisons with the hemicurcuminoid derivatives show that the two‐photon active band for the curcuminoid derivatives has the same intramolecular charge‐transfer character and therefore arises from a dipolar structure. Overall, this structure–relationship study allows the optimization of the two‐photon brightness (i.e., 400–900 GM) with one dye that emits in the NIR region of the spectrum. In addition, these dyes demonstrate high intracellular uptake efficiency in Cos7 cells with emission in the visible region, which is further improved by using porous silica nanoparticles as dye vehicles for the imaging of two mammalian carcinoma cells type based on NIR fluorescence emission. Abstract : Very bright : The influence of different donor (D) and acceptor (A) groups of boron difluoride complexes containing curcuminoid derivatives on the UV/Vis absorption and fluorescence behavior is investigated by using experimental and theoretical methods. Selected compounds were also investigated as cell imaging probes (see figure).